Effect of Magnetic Field on Blood Flow in Stenoted Arteries - Rotaina Essa (Al-Rafidain Journal of Computer Sciences and Mathematics, 2019)
In this paper, the effect of magnetic field on blood flow in stenoted arteries was studied, stokes equations in polar coordinates were used to describe such flow. All flow characteristics were found under the influence of the magnetic field and how this stenosis affects flow.